The boost of force in unfused tetanic contractions at variable interpulse intervals in fast motor units of the rat medial gastrocnemius - K. Kryściak; J. Celichowski; R. Raikova; H. Drzymała-Celichowska (Scientific Reports)
Abstract Previously, boost and sag effects seen in unfused tetanic contractions have been studied exclusively at constant stimulation frequency. However, intervals between successive discharges of motoneurons vary during voluntary movements. We therefore aimed to test whether the extra-efficient force production at the onset of contraction (boost) occurs during stimulation with variable intervals, and to what extent it depends on the level of interpulse interval (IPI) variability and history of stimulation. Four sets of three repeated unfused tetani (the first set with constant IPIs at 35 Hz; the other three sets with mean frequency 35 Hz and variable IPIs 28 ± 2 ms, ± 5 ms, and ± 7 ms, respectively) were recorded with 3 min breaks in fast fatigable and fast fatigue-resistant motor units of the rat medial gastrocnemius. We show that boost occurred in the first tetanic contraction of each set for stimulation at both constant and variable IPIs in two fast types of motor units; additionally, it was present in different IPIs variability for a given range. Mathematical decomposition of first (sagging) and second (non-sagging) tetanic contractions into twitch-like responses to successive stimuli in the tested IPIs variability showed that the changes underlying boost are pattern independent. This implies that boost probably occurs in daily activity when motoneurons fire with an unstable firing rate. The effect may therefore contribute to the development and regulation of force in voluntary daily activities, especially in short powerful contractions.